Embodied Ways of Listening: Oral History, Genocide and the Audio Tour - High, Steven (Anthropologica, 2013)
Building on the work of sound artists Miller and Cardiff, oral historian Butler, as well as the broader insights gleaned from the Montréal Life Stories project, this paper con siders space-time dissonance in the making of Une Fleur dans le Fleuve / A Flower in the River, a 53 minute audio walk fol lowing the same commemorative path taken by the Rwandan community. The tour explores the personal meaning and legacy of mass violence through personal narratives of six Rwandan exiles and survivors. The audio tour produces for the listener the same kind of dissonance that Rwandan Montréalers live out on a day-to-day basis.